Midazolam and ketamine produce distinct neural changes in memory, pain, and fear networks during pain - Vogt, Keith M. (Anesthesiology, 2021)
INTRODUCTION: Despite the well-known clinical effects of midazolam and ketamine, including sedation and memory impairment, the neural mechanisms of these distinct drugs in humans are incompletely understood. We hypothesized that both drugs would decrease recollection memory, task-related brain activity, and long-range connectivity between components of the brain systems for memory encoding, pain processing, and fear learning. METHODS: In this randomized within-subject crossover study of 26 healthy adults, we used behavioral measures and functional magnetic resonance imaging to study these two anesthetics, at sedative doses, in an experimental memory paradigm employing periodic pain. The primary outcome, recollection memory performance, was quantified with dʹ (a difference of Z-scores between successful recognition versus false identifications). Secondary outcomes were: familiarity memory performance, serial task response times, task-related brain responses and underlying brain connectivity from 17 pre-selected anatomical seed regions. All measures were determined under saline and steady-state concentrations of the drugs. RESULTS: Recollection memory was reduced under midazolam (dʹ = 0.73 [0.43, 1.02], median [95% confidence interval]), compared to saline (dʹ = 1.78 [1.61, 1.96]) and ketamine (dʹ = 1.55 [1.12, 1.97], P < 0.0001). Task-related brain activity was detected under saline in areas involved in memory, pain, and fear, particularly the hippocampus, insula, and amygdala. Compared to saline, midazolam increased functional connectivity to 20 brain areas and decreased to 8, from seed regions in the precuneus, posterior cingulate, and left insula. Compared to saline, ketamine decreased connectivity to 17 brain areas and increased to 2, from 8 seed regions including the hippocampus, parahippocampus, amygdala, and anterior and primary somatosensory cortex. CONCLUSIONS: Painful stimulation during light sedation with midazolam, but not ketamine, can be accompanied by increased coherence in brain connectivity, even though details are less likely to be recollected as explicit memories.